Practice of non-drug pain management in nursing care of critically ill orthopedic patients (骨科危重患者非药物疼痛护理管理实践) - WANG Yanke (王艳可); ZHANG Xuejian (张雪键); LIU Ai (刘爱); CUI Yangfang (崔杨芳); LIU Hongli (刘红丽); ZHAO Yue (赵月) (Association of Integrative Nursing, 2021)
Objective To observe the practice effect of non-drug pain management in nursing care of critically ill orthopedic patients. Methods Totally 68 critically ill orthopedic patients were included as research objects. The non-drug pain management was carried out on the basis of routine nursing for pain control. The pain relief and adverse reactions were observed after intervention, and patient's satisfaction with nursing was measured. Results All patients recovered well, and there was no case of insomnia, constipation, headache reported. The score of pain assessment scale and frequency of acute pain were decreased after intervention. The overall rate of satisfaction was 94. 12%(64/68). Conclusion On the basis of routine pain control, the non-drug pain management is potentially effective to relieve the pain intensity of critically ill orthopedic patients. (目的 探讨骨科危重患者非药物疼痛护理管理实践效果。方法 选取科室收治的68例骨科危重患者为研究对象, 在常规护理基础上增加非药物疼痛护理干预。评估患者疼痛缓解情况, 记录不良反应发生情况, 评价患者对护理的满意度。结果 患者术后恢复良好, 未出现失眠、便秘、头痛等并发症或不良反应。患者疼痛评分降低, 急性疼痛发生次数减少。满意度评价结果显示, 患者总满意度为94. 12%(64/68)。结论 在常规护理的基础上, 非药物疼痛护理干预能进一步改善骨科危重患者疼痛程度, 促进患者康复。)